Hydrogel Microneedle Arrays for Transdermal Drug Delivery - Hong, Xiaoyun; Wu, Zaozhan; Chen, Lizhu; Wu, Fei; Wei, Liangming; Yuan, Weien (Nano-Micro Letters, 2014)
Stratum corneum is the main obstacle for drugs to pass through the skin. Microneedles are composed of arrays of micro-projections formed with different materials, generally ranging from 25–2000 μm in height. Microneedles straightly pierce the skin with its short needle arrays to overcome this barrier. Microneedles can be divided into several categories, for instance, solid microneedles, coated microneedles, and hollow microneedles and so on. However, all these types have their weak points related to corresponding mechanisms. In recent years, pioneering scientists have been working on these issues and some possible solutions have been investigated. This article will focus on the microneedle arrays consisting of hydrogels. Hydrogels are commonly used in drug delivery field. Hydrogel microneedles can be further divided into dissolving and degradable microneedles and phase transition microneedles. The former leaves drug with matrix in the skin. The latter has the feature that drugs in the matrix are delivered while the remaining ingredients can be easily removed from the skin after usage. For drugs which are required to be used every day, the phase transition microneedles are more acceptable. This article is written in order to summarize the advantages of these designs and summarize issues to be solved which may hinder the development of this technology.